Upaya meningkatkan hasil belajar PKn melalui penerapan model pembelajaran kelompok bongkar pasang bagi siswa kelas V sekolah dasar - Puryono, Puryono (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2020)
The purpose of this study was to determine the efforts to improve Civics learning outcomes through the application of the Unloading Group learning model for fifth grade students of SD Negeri 2 Carikan Juwiring Klaten in the first semester of the 2018/2019 academic year. This research is a classroom action research (PTK) with the research subject being the fifth grade students of SD Negeri 2 Carikan Juwiring Klaten in the first semester of the 2018/2019 academic year. The data collection techniques used in this study were (1) field relations techniques, (2) participatory observation, (3) interviews, (4) divergent thinking. The collected data were analyzed using descriptive analysis. Based on the data analysis, it can be concluded that from the theoretical or empirical truth that the researchers obtained, then through the Application of the Unloading Group Learning Model can improve the learning outcomes of Civics class V SD Negeri 2 Carikan Juwiring Klaten in the first semester of the2018/2019 learning year. seen in the results of the scores after they carried out the post test. The results are: a) The lowest score = 75, b) The highest score = 90, c) The average value = 80. From the data above, it shows a significant increase because the results obtained by students which are an average value increase to 24 points.